Pemberdayaan Masyarakat Kampung Yuboi melalui Pelatihan Produksi dan Diversifikasi Olahan Ulat Sagu dan Mujair Asap - Agus Zainuri; Rosmin Mariati Tingginehe; Selli Reni Andeina (Joong-Ki : Jurnal Pengabdian Masyarakat, 2025)
This community service program was implemented in Yoboi Village with the aim of enhancing community skills, particularly among members of the Family Welfare Movement (PKK), in processing local food resources such as smoked tilapia and smoked sago larvae into innovative processed products, including meatballs and nuggets. In addition, the program sought to provide education on nutrition and food safety, promote household economic empowerment through the establishment of small-scale, local food–based microenterprises (UMKM), and optimize the potential of local food resources to generate added economic and nutritional value while preserving the local wisdom of the Yoboi community. The program employed several methods, including nutrition education on the importance of utilizing local food resources, demonstrations and hands-on training in processing smoked tilapia and smoked sago larvae, direct practice by participants, and group discussions on product marketing strategies. The participants consisted of 15 housewives and PKK members from Yoboi Village. The results indicated an improvement in participants’ knowledge and skills in processing local food into value-added products. Participants were able to independently produce sago larvae meatballs and smoked tilapia nuggets. Furthermore, the community gained an understanding of marketing strategies and demonstrated a commitment to establishing small-scale enterprises based on local food resources.In conclusion, the program successfully enhanced nutritional awareness, technical skills, and economic motivation among the Yoboi community. Community empowerment through local food processing has the potential to support household food security while simultaneously creating new business opportunities rooted in local wisdom.